2017
DOI: 10.1002/maco.201709461
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for long‐time degradation of magnesium under physiological conditions

Abstract: The present work applies the law of mass conservation toward an analytical model describing the long‐term degradation of Mg‐0.3Ca implant material in defined physiological electrolyte environments. The model takes into account surface conversion and degradation product deposition related changes of degradation rates by introducing an effective layer thickness. The analytical nature of the approach does not consider detailed chemical and electrochemical process. Thus, it simply declares an effective damping ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Under static conditions degradation analysis is performed in the same medium during the whole immersion time [ 91 ] or by entirely or partially replacing it with fresh medium during the immersion time (semi-static) [ 7 , 100 , 102 ]. In these cases, mass transfer between the surface region and the bulk medium is controlled by the processes of migration, diffusion and a certain degree of convection generated by the H 2 evolution from the surface according to the cathodic reaction (Equation (2) ).…”
Section: To Flow or Not To Flow? The Question Of Experimental Setupsmentioning
confidence: 99%
“…Under static conditions degradation analysis is performed in the same medium during the whole immersion time [ 91 ] or by entirely or partially replacing it with fresh medium during the immersion time (semi-static) [ 7 , 100 , 102 ]. In these cases, mass transfer between the surface region and the bulk medium is controlled by the processes of migration, diffusion and a certain degree of convection generated by the H 2 evolution from the surface according to the cathodic reaction (Equation (2) ).…”
Section: To Flow or Not To Flow? The Question Of Experimental Setupsmentioning
confidence: 99%
“…The corrosion rate is given by yGSGtrue′(t)=1τ(dnormal∞yGSG(t))=dτnormalet/τ.A similar expression is also used to model the influence of corrosion products on aluminum via FEM simulations Nidadavolu et al and Dahms et al,the empirical expression of the corrosion progress given by Nidadavolu et al and Dahms et al has the following implicit form ynormalN(t)=y0(1normaleynormalN(t)/y0)+trueẏnormal∞t.y0 is the corrosion depth on short time scales and ẏ is the long‐term corrosion rate. The implicit corrosion rate is given by ynormalNtrue′(t)=ẏ1normaleynormalN(t)/normaly0where the parameter y 0 describes the initial period which is driven by electrode kinetics and ẏ the steady‐state situation which is determined by a limiting process again. Brown et al and Barnard et al,in this FEM simulation the corrosion rate hindered by corrosion products, for example zinc hydroxide, is given by yBBtrue′(t)=a(1p)2=a(1byBB(…”
Section: Computational Modelingmentioning
confidence: 99%
“…Modeling of corrosion processes is a research subject of great interest and has applications among others in automotive industry, marine industry, and medical industry . There are various approaches to compute the corrosion progress.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies of similar problems for a range of metals that neglect the advective contribution to the corrosion dynamics, resulting in Stefan-like problems to describe corrosion in, for example, zirconium [ 20 ] and steel [ 21 ]. Magnesium corrosion has been the subject of a small number of modelling studies [ 22 , 23 , 24 ]. In [ 23 ], a simple two-phase bulk model of magnesium corrosion was proposed and parameter fitted to experimental data; however, the model is not explicit in the products of corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium corrosion has been the subject of a small number of modelling studies [ 22 , 23 , 24 ]. In [ 23 ], a simple two-phase bulk model of magnesium corrosion was proposed and parameter fitted to experimental data; however, the model is not explicit in the products of corrosion. A spatially explicit model of a galvanised magnesium was proposed in [ 24 ]; here, the magnesium block was a fixed domain and they showed that the thickness of the galvanised layer affected corrosion.…”
Section: Introductionmentioning
confidence: 99%